(3CPcGQ GdCPcGQs - (3GdSjhWj GdNVjQj, CHh GdaVd, LdGd GdOjf, YHO GdQMef Hf CHj HcQ Hf eMeO, J (B911 (3g`s
(3ChdgG (B:s
(3hLGgOJ aj Gddg JYGdi Mb LgGOg Gddge BJg GdhSjdI hGdaVjdI hGHYKg ebGeG eMehOG GdPj hYOJgs
(3BNQgG (B:s
(3ef GdTQ hJHGYOj ef GdLaQ hCfj dG CKb EdG HQMeJc aGLYdg dj YfOc YgOG JDOjg Edi jhe GdbjGeI Efc dG JNda GdejYGOs
(3efbhdI Yf fSNI GdeDda GdeDQNI (B886 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3 / 301s
(3eYLe GdeDdajf (B2 / 82s
(3cTa GdXfhf (B1 / 51s
(3TPQGJ GdPgH (B8 / 51s
Keywords: (3GdMOjK hGdeUWdMs